(3RgQI Gdebhd aI fSH KGfi aQYi GdQShds - (3Rjf GdOjf Ydj Hf GdMSf Hf TObe GdMeRi GdeOfjs; (3VGef Hf TObe Hf Ydj Hf MSf Hf GdfbjH GdeOfj GdMeRj GdMSjfj, GHf TObe,J (B1088 (3g` ? s
(3ChdgG (B:s
(3hHYO adeG WGdYJ hJCedJ eDda hGdOi bOS SQg hGdeSei HGdeSJWdHI ai fSH SGOGJ WGHI , hLOJg eNJUQkG aCMHHJ GdJjef HehGbY fXQg s
(3BNQgG (B:s
(3JeJ hcedJ GdQSGdI , hCfG CSJZaQ Gddg ef RjZ GdebGdI s
(3GdPQjYI (B:(3L(B12 (3U(B76s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B213s
(3GdPQjYI (B- (3GdLRA (B12 - (3U (B76 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B224 s
Keywords: (3GdJGQjNs